2020
DOI: 10.1002/tox.22897
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidic acid induces apoptosis in human nasopharyngeal carcinoma cells through p38‐mediated upregulation of caspase activation

Abstract: Cantharidic acid (CA) is the hydrolysis product of the acid anhydride cantharidin, which is a natural toxin secreted by several species of blister beetles. Several studies have indicated that as an inhibitor of protein phosphatase 2 (PP2A), CA induces apoptosis in various human cancer cells. However, the effect of CA on human nasopharyngeal carcinoma (NPC) cells and the underlying pathways have not been addressed. In our current study, we tested the hypothesis that CA treatment reduces the viability of human N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Treatment with celastrol, a traditional Chinese medicinal plant, was also found to significantly increase the phosphorylation of p38 MAPK and JNK1/2 in cisplatin-resistant human NPC-039 and NPC-BM NPC cells, triggering cytotoxicity by activation of caspasemediated apoptotic pathways in these cells [119]. Cantharidic acid, a natural toxin secreted by beetles, has proven to reduce NPC cell viability through the upregulation of caspase activation in extrinsic and intrinsic apoptosis pathways, as well as the upregulation of p38 and JNK1/2 pathways [120]. Treatment with licochalcone A significantly promoted cell apoptosis by increasing p38 and JNK1/2 activation and upregulated caspase-3, caspase-8, caspase-9 activation, and cleaved-PARP expression [121].…”
Section: Tumor Suppressive Functions Of Jnk and P38 Mapk Signaling In...mentioning
confidence: 99%
“…Treatment with celastrol, a traditional Chinese medicinal plant, was also found to significantly increase the phosphorylation of p38 MAPK and JNK1/2 in cisplatin-resistant human NPC-039 and NPC-BM NPC cells, triggering cytotoxicity by activation of caspasemediated apoptotic pathways in these cells [119]. Cantharidic acid, a natural toxin secreted by beetles, has proven to reduce NPC cell viability through the upregulation of caspase activation in extrinsic and intrinsic apoptosis pathways, as well as the upregulation of p38 and JNK1/2 pathways [120]. Treatment with licochalcone A significantly promoted cell apoptosis by increasing p38 and JNK1/2 activation and upregulated caspase-3, caspase-8, caspase-9 activation, and cleaved-PARP expression [121].…”
Section: Tumor Suppressive Functions Of Jnk and P38 Mapk Signaling In...mentioning
confidence: 99%
“…However, the activation of ERK can also induce cell apoptosis by regulating mitochondrial cytochrome c release and caspase-8 activation [ 42 ]. In our previous studies, many anticancer compounds were found to activate p-ERK and induce apoptosis in different types of cancer [ 38 , 43 ]. The activation of ERK can also reportedly induce cell-cycle arrest, which may cause apoptosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ERK1/2, p38, and c‐Jun N‐terminal kinase 1/2 (JNK1/2) pathways were up‐regulated. These results indicated that CA treatment induced apoptosis of human NPC cells through up‐regulation of caspase activation, especially through p38 pathway‐mediated caspase activation (Chen et al., 2020).…”
Section: Natural Products That Target Nasopharyngeal Carcinomamentioning
confidence: 95%
“…Cantharidic acid (CA) is the product of hydrolysis of the acid anhydride cantharidin, which is a natural toxin secreted by several blister beetles (Chen et al., 2020). CA significantly reduced the viability of NPC cells and the activation of caspase in exogenous and endogenous apoptotic pathways.…”
Section: Natural Products That Target Nasopharyngeal Carcinomamentioning
confidence: 99%